2020
DOI: 10.1093/jhps/hnaa030
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative comparisons for a return to running protocol in recreational athletes following hip arthroscopy

Abstract: The purpose of the current study was to present pre-operative comparisons for recreational athletes attempting a return to running following hip arthroscopy, and the return to running progression protocol used to guide them. A prospective, non-randomized cohort study was conducted to evaluate recreational athletes that returned to running following hip arthroscopy. Return to running was the primary outcome measure and defined as the ability to run at least one mile three times weekly while maintaining patient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Although the shoulder joint is not a direct load-bearing joint during running, running imparts loads on the shoulder that require coordinated contraction of the dynamic stabilizers of the glenohumeral joint to maintain concentric reduction of the glenohumeral joint. Although prior studies have reported on return to running after knee and hip surgery, 1 , 2 little is known regarding return to running after shoulder surgery. Numerous studies have reported on RTS after arthroscopic and open shoulder surgery with a common timeline of 5 to 6 months.…”
mentioning
confidence: 99%
“…Although the shoulder joint is not a direct load-bearing joint during running, running imparts loads on the shoulder that require coordinated contraction of the dynamic stabilizers of the glenohumeral joint to maintain concentric reduction of the glenohumeral joint. Although prior studies have reported on return to running after knee and hip surgery, 1 , 2 little is known regarding return to running after shoulder surgery. Numerous studies have reported on RTS after arthroscopic and open shoulder surgery with a common timeline of 5 to 6 months.…”
mentioning
confidence: 99%